2019
DOI: 10.1002/slct.201901477
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Dynamic Capture of Antibiotics by Conjugated Microporous Polymers

Abstract: The encapsulation of antibiotic molecules in conjugated microporous polymers is investigated by using the density functional theory (DFT) method and molecular dynamics (MD) simulations. We find that guest molecules are firstly wrapped around the edges of the polymer nanopores, and as the number of guest molecules increases, they begin to move from the edge to the center of the pore to further stabilize the complex. We discover a parallel sandwich‐type encapsulation model, it is the most stable configuration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The high specific surface are (519.7 m 2 g −1 ) and high porosity of the MTCMP also contributed to its good adsorption capacity. In 2019, Li et al 161 studied the capture of antibiotic molecules by CMP using density functional theory and molecular dynamics simulation. They found that a parallel sandwich wrapper model was the most stable object molecule in the mainframe configuration skeleton.…”
Section: ■ Application Of Cmps In Adsorption Sciencementioning
confidence: 99%
“…The high specific surface are (519.7 m 2 g −1 ) and high porosity of the MTCMP also contributed to its good adsorption capacity. In 2019, Li et al 161 studied the capture of antibiotic molecules by CMP using density functional theory and molecular dynamics simulation. They found that a parallel sandwich wrapper model was the most stable object molecule in the mainframe configuration skeleton.…”
Section: ■ Application Of Cmps In Adsorption Sciencementioning
confidence: 99%